Awareness of Sustainable Development Related Themes in Selected African Literature-in English Texts among Senior Secondary School Students in Nigeria (2023)
This study, hinged on the tenets of the sociology of Literature, examined the portrayal of themes related to Sustainable Development Goals (SDGs, henceforth) in two (Lonely Days and Harvest of Corruption) African Literature-in-English texts recommended for Nigerian senior secondary school students from 2016-2020. The purpose of the study was to investigate students’ awareness of the SDGs-related themes that are portrayed in the selected text. The study adopted a mixedmethods research design. Quantitative data were collected from 150 Literature-in-English students, using a Questionnaire on Students’ Awareness of Sustainable Development Themes in Literaturein-English Texts (r = 0.73 and analysed using descriptive statistics. The two selected texts were also analysed thematically. Findings revealed that students’ awareness of the sustainable development themes in the texts was low despite the high portrayal of such themes (corruption, unemployment, justice, women’s subjugation and inequality, women’s economic independence,empowerment, and environmental degradation) in the texts. It was recommended that Literaturein-English teachers should emphasise the themes students and the citizenry at large could learn from the prescribed texts.